Endometriosis-Associated Ovarian Carcinomas: How PI3K/AKT/mTOR Pathway Affects Their Pathogenesis - Tatiana S. Driva; Christoph Schatz; Johannes Haybaeck (Biomolecules, 2023)
Ovarian clear cell (OCCC) and endometrioid (EnOC) carcinomas are often subsumed under the umbrella term “endometriosis-associated ovarian cancer” (EAOC), since they frequently arise from ectopic endometrium settled in the ovaries. The phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway is known to be aberrantly activated both in endometriosis and EAOC; however, its role in the progression of endometriosis to ovarian cancer remains unclear. In fact, cancer-associated alterations in the mTOR pathway may be found in normal uterine epithelium, likely acting as a first step towards ovarian cancer, through the intermediary stage of endometriosis. This review aims to summarize the current knowledge regarding mTOR signaling dysregulation in the uterine endometrium, endometriosis, and EAOC while focusing on the interconnections between the PI3K/AKT/mTOR pathway and other signaling molecules that give rise to synergistic molecular mechanisms triggering ovarian cancer development in the presence of endometriosis.